Ex-vivo biomechanical testing of pig femur diaphysis B type fracture fixed by novel biodegradable bone glue - Krtička, Milan; Michlovská, Lenka; Nekuda, Vladimír; Poláček, Petr; Valová, Kristýna; Žídek, Jan; Kaiser, Jozef; Zikmund, Tomáš; Vojtová, Lucy (Journal of the mechanical behavior of biomedical materials, 2021)
AIMS: The aim of this study was to answer the question whether our newly developed injectable biodegradable "self-setting" polymer-composite as a bone adhesive is a good "bone-glue" candidate to efficiently fix comminuted fractures of pig femoral bones used as an ex-vivo experimental model. METHODS: Mechanical properties of adhesive prepared from α-tricalcium phosphate (TCP) powder and thermogelling copolymer were optimized by selecting the appropriate composition with adhesion enhancers based on dopamine and sodium iodinate. Setting time and injectability were controlled by rheology. Ex-vivo experiments of fixed pig bones were provided in terms of either the three-point bending test of bending wedge type fractured pig femurs (with LCP) or the axial compression test of 45° oblique fractured femurs (without LCP) in physiological saline solution at 37 °C. Fractured bones treated with optimized adhesive before and after bending tests were imaged by X-ray microtomography (μCT). RESULTS: Based on the rheological measurement, the adhesive modified with both dopamine and sodium iodinate exhibited optimal thixotropic properties required for injection via thin 22 G needle. This optimal adhesive composition showed an 8 min lag phase (processing time) followed by fast increase in storage modulus at 37 °C up to 1 GPa within 110 min. Self-setting of dopamine/iodinate modified adhesive was completed in 48 h exhibiting the maximum strength at compression of 7.98 MPa ± 1.39 MPa. Whereas unmodified adhesive failed in glue-to-bone adhesion, dopamine and dopamine/iodinate modified adhesive used for 45° oblique fracture fixation showed good and similar strength at compression (3.05 and 2.79 MPa, respectively). However, significantly higher elasticity of about 250% exhibited adhesive with iodinate enhancer. Moreover, mechanical properties of B2 fractures fixed with both LCP and dopamine/iodinate adhesive were approaching closely to the properties of original bone. Excellent adhesion between the adhesive and the bone fragments was proved by μCT. CONCLUSION: The polymer-composite bone adhesive modified with dopamine/iodinate exhibited very good fixation ability of femoral artificial comminuted fractures in an experimental model.
Keywords: diafýzy; Fracture Fixation, Internal; Femoral Fractures; Fracture Fixation; Biodegradable polymer; Adhesive; Ex-vivo; Rheology; zvířata; fraktury femuru; Thixotropy; kostní cementy; Swine; femur; Biomechanics; vnitřní fixace fraktury; Femur; Bone Plates; kostní destičky; Bone Cements; Diaphyses; fixace fraktury; Bone; Animals; Microtomography; biomechanika; Biomechanical Phenomena; Fracture; prasata